Unveiling New Process Impurities in Ripasudil Hydrochloride Dihydrate: Identification, Synthesis, and Characterization - Birajdar, Kedarnath M.; Arrahalli, Sudhakar; Mokshanatha, Praveen Beekanhalli; Babu, Prashanth Kumar (Current Organic Synthesis, 2025)
BackgroundRipasudil hydrochloride or 4-Fluoro-5-[(2S)-2-Methyl-1,4-diazepan-1-yl] sulfonyl isoquinoline hydrochloride known as K-115 is used for the treatment of glaucoma and ocular hypertension. In the API industry, to achieve and ensure the quality of drug substances, there is a need for impurity identification, synthesis, and characterization. The impurities are formed during the process, either side reaction or degradation or carried over from the starting material.ObjectivesThe present study explores two new process impurities of Ripasudil Hydrochloride dihydrate, specifically Impurity-1(4-fluoro-5-[(3R)-3-methyl-4-(2-nitrolbenzenesulfonyl)-1,4-diazepan-1-yl] sulfonyl isoquino line) and Impurity-2 (4-fluoro-N, N-dimethyl isoquinoline-5-sulfonamide). These impurities are critical to the quality of both the drug substance and the final drug product.MethodsThe API crude samples were subjected to LC-mass spectrometry for the identification of unknown impurities and further based on the observed mass values, a strategic synthetic route was designed for the synthesis of unknown impurities. The synthetic routes for these impurities were developed to avoid column purification, achieving high yields and purity.ResultsThe above synthesized impurities were subjected to spectral analysis like mass spectrometry, 1H NMR, and 13C NMR and confirmed the desired structure of the unknown impurities. So, as far as we know, the two impurities are new process impurities and have not been reported in the literature.ConclusionThe two new process impurities have been prepared and used as impurities for the method development and quality evaluation of the Ripasudil drug substance. Given the regulatory significance of Ripasudil hydrochloride, our successful synthesis and characterization efforts have proven to be valuable. This research offers valuable insights into the generic pharmaceutical industry.",
Keywords: HPLC